Accidental Subcutaneous Remifentanil Infusion as a Cause of Delayed Awakening after Craniotomy - Alexander Wolfson; Cephas Swamidoss (Case Reports in Anesthesiology)
We report a case of accidental subcutaneous infusion of remifentanil as a cause of delayed awakening after a craniotomy.